The Leadership Developments Process for Sustainable Community Forest Management in Nakhon Ratchasima Province - et. al., Pramaha Prakasit Thitipasitthikorn, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research, the objective of this study was to study the role of forest masters in the management of model community forests in Nakhon Ratchasima Province. And to propose a leadership development process for sustainable community forest management in Nakhon Ratchasima Province. It is qualitative research. By conducting in-depth interviews with local philosophers, community leaders, community forest committee, and villagers in the area totaling 30 persons and conducting a specific group discussion with 15 persons. The data collection tool used structured interviews. And to analyze expository data using the Samsao technique. The results of the research show that 1) Forest scholars played a role in the management of model community forests in Nakhon Ratchasima Province, as a representative role of the community. Role as a motivator Negotiator role, role as a teacher, the role of the team builder, the role of problem-solver, and the role of supervisor. Thus, enabling efficient management of the model community forest the community participated in the proper utilization of resources and the community realized the shared value of community resources through the leadership of forest masters. 2) Leadership development process for sustainable community forest management in Nakhon Ratchasima Province. It consists of 5 important processes called the "KLIPS Model": (1) The knowledge management process (K = Knowledge) (2) The leadership formation process (L = Leadership) (3) The innovation development process (I = Innovation) (4) The Participation process (P = Participation) and (5) The Networking process (S = Social Networks)